Adaptation of Benefits to the Needs of Employees in Companies in Serbia - Radovanović, Olga (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
Abstract:.The benefits that companies provide to employees are most often based on the principle of "one size fits all" and relate mainly to the same offer of benefits for all employees. Companies do not ask employees what their needs are and what the benefits would mean to them, so the aim of the research was to determine the current state of benefits in companies, tailoring to their needs and the importance of personalization to take advantage of the benefits offered. Research has been conducted in September 2020 on two samples: The first sample includes 109 HR managers and Compensation and benefit managers (Comp & Ben Managers) and the second survey was conducted on a sample of 204 employees in companies. The results indicate concrete steps that human resource managers can implement in their companies to positively impact their employees.